Molecular engineering of PETase for efficient PET biodegradation - Tao Wang; Wen-tao Yang; Yu-ming Gong; Ying-kang Zhang; Xin-xin Fan; Guo-cheng Wang; Zhen-hua Lu; Fei Liu; Xiao-huan Liu; You-shuang Zhu (Ecotoxicology and Environmental Safety, 2024)
The widespread utilization of polyethylene terephthalate (PET) has caused a variety of environmental and health problems. Compared with traditional thermomechanical or chemical PET cycling, the biodegradation of PET may offer a more feasible solution. Though the PETase from Ideonalla sakaiensis (IsPETase) displays interesting PET degrading performance under mild conditions; the relatively low thermal stability of IsPETase limits its practical application. In this study, enzyme-catalysed PET degradation was investigated with the promising IsPETase mutant HotPETase (HP). On this basis, a carbohydrate-binding module from Bacillus anthracis (BaCBM) was fused to the C-terminus of HP to construct the PETase mutant (HLCB) for increased PET degradation. Furthermore, to effectively improve PET accessibility and PET-degrading activity, the truncated outer membrane hybrid protein (FadL) was used to expose PETase and BaCBM on the surface of E. coli (BL21with) to develop regenerable whole-cell biocatalysts (D-HLCB). Results showed that, among the tested small-molecular weight ester compounds (p-nitrophenyl phosphate (pNPP), p-Nitrophenyl acetate (pNPA), 4-Nitrophenyl butyrate (pNPB)), PETase displayed the highest hydrolysing activity against pNPP. HP displayed the highest catalytic activity (1.94 μM(p-NP)/min) at 50 °C and increased longevity at 40 °C. The fused BaCBM could clearly improve the catalytic performance of PETase by increasing the optimal reaction temperature and improving the thermostability. When HLCB was used for PET degradation, the yield of monomeric products (255.7 μM) was ∼25.5 % greater than that obtained after 50 h of HP-catalysed PET degradation. Moreover, the highest yield of monomeric products from the D-HLCB-mediated system reached 1.03 mM. The whole-cell catalyst D-HLCB displayed good reusability and stability and could maintain more than 54.6 % of its initial activity for nine cycles. Finally, molecular docking simulations were utilized to investigate the binding mechanism and the reaction mechanism of HLCB, which may provide theoretical evidence to further increase the PET-degrading activities of PETases through rational design. The proposed strategy and developed variants show potential for achieving complete biodegradation of PET under mild conditions.